2007
DOI: 10.1021/jf062010a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Source and Level in Hen's Diet on Tissue Selenium Deposition and Egg Selenium Concentrations

Abstract: The present study was conducted in a 2 x 4 factorial arrangement in a randomized complete block (RCB) design to compare the effects of a commercial inorganic Se source (sodium selenite, SS) with a commercial organic Se source (Se-enriched yeast, SY) on tissue Se distribution and blood and whole-egg Se concentrations in laying hens. Both Se sources were added into the basal diet at 0, 0.2, 0.5, and 1.0 mg/kg of Se. Seven hundred 68 week old Rohman laying hens were fed with a basal diet containing 0.15 mg/kg DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
57
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 22 publications
19
57
0
1
Order By: Relevance
“…Selenium content of blood and plasma The lack of any significant response in blood and plasma Se concentrations of unsupplemented birds would be expected and is consistent with the findings of other authors investigating the effects of supplementary Se on poultry (Echevarria et al, 1988;Pan et al, 2007;Yoon et al, 2007). The differences seen between comparable doses of the different Se supplements from the current study are indicative of better uptake and incorporation of Se derived from SY and are consistent with findings in sheep (Van Ryssen et al, 1989;Juniper et al, 2008a), cattle (Gunter et al, 2003;Juniper et al, 2008b;Phipps et al, 2008) and pigs (Kim and Mahan, 2001).…”
Section: Feed Analysessupporting
confidence: 92%
See 4 more Smart Citations
“…Selenium content of blood and plasma The lack of any significant response in blood and plasma Se concentrations of unsupplemented birds would be expected and is consistent with the findings of other authors investigating the effects of supplementary Se on poultry (Echevarria et al, 1988;Pan et al, 2007;Yoon et al, 2007). The differences seen between comparable doses of the different Se supplements from the current study are indicative of better uptake and incorporation of Se derived from SY and are consistent with findings in sheep (Van Ryssen et al, 1989;Juniper et al, 2008a), cattle (Gunter et al, 2003;Juniper et al, 2008b;Phipps et al, 2008) and pigs (Kim and Mahan, 2001).…”
Section: Feed Analysessupporting
confidence: 92%
“…Glandular visceral tissues tend to have greater total Se concentrations than muscle, and cardiac muscle has a greater total Se content than skeletal muscle. These data agree with those reported in laying hens (Petrovič et al, 2006;Pan et al, 2007) and broilers (Wang and Xu, 2008) and are also similar to those reported in lambs (Juniper et al, 2008a) and beef cattle (Juniper et al, 2008b). The differences seen in cardiac, skeletal and gizzard muscle tissue total Se concentrations, when comparing comparable doses of the two sources of Se, are indicative of improved Se uptake and incorporation within those birds supplemented with SY.…”
Section: Selenium Content In Tissuessupporting
confidence: 89%
See 3 more Smart Citations